2015
DOI: 10.1095/biolreprod.115.130542
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of DNA Double-Strand Breaks Is Higher in Late-Cleaving and Less Developmentally Competent Porcine Embryos1

Abstract: Studies in different species, including human, mice, bovine, and swine, demonstrated that early-cleaving embryos have higher capacity to develop to the blastocyst stage and produce better quality embryos with superior capacity to establish pregnancy than late-cleaving embryos. It has also been shown that experimentally induced DNA damage delays embryo cleavage kinetics and reduces blastocyst formation. To gain additional insights into the effects of genome damage on embryo cleavage kinetics and development, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 49 publications
6
30
1
Order By: Relevance
“…Therefore, we hypothesized that CDK2 knockdown-induced cell cycle arrest may be caused by increased accumulation of DNA damage during early embryonic development. Indeed, by analyzing the number of γH2AX fluorescent foci [37,38], we demonstrated that CDK2 knockdown embryos have more DNA DSBs than control embryos on days 3 and 5 of development. In response to DNA damage, cell cycle checkpoints (G1, S, G2/M) are activated, stopping cell cycle progression to allow time for repair, thereby preventing transmission of damaged or incompletely replicated chromosomes [3].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we hypothesized that CDK2 knockdown-induced cell cycle arrest may be caused by increased accumulation of DNA damage during early embryonic development. Indeed, by analyzing the number of γH2AX fluorescent foci [37,38], we demonstrated that CDK2 knockdown embryos have more DNA DSBs than control embryos on days 3 and 5 of development. In response to DNA damage, cell cycle checkpoints (G1, S, G2/M) are activated, stopping cell cycle progression to allow time for repair, thereby preventing transmission of damaged or incompletely replicated chromosomes [3].…”
Section: Discussionmentioning
confidence: 96%
“…Cleavage stage embryos have few DNA breaks and low transcription levels for DNA repair and cell cycle checkpoint proteins23. These peculiarities in cleavage stage development can influence embryonic response to genetic insults7.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that early developing embryos can respond to DSBs by inducing the phosphorylation of histone H2A.x and activating checkpoint proteins, Chek1 and Chek2, which block the cell cycle to prevent the segregation of DSBs in dividing cells (5, 14, 31, 32). Moreover, we have observed that early developing embryos can respond to DNA damage by up‐regulating the expression of genes that are involved in either the HR or NHEJ pathways (2, 4); however, it has not been determined if both pathways are required for DSB repair in early embryos before the first cell lineage specification. In pluripotent embryonic stem cells, which are derived from blastocysts after the first cell lineage specification, HR is the predominant pathway for DSB repair (33).…”
mentioning
confidence: 99%